Surveillance, Epidemiology, and End Results (SEER) and SEER-Medicare Databases: Use in Clinical Research for Improving Colorectal Cancer Outcomes - Daly, Meghan C.; Paquette, Ian M. (Clinics in Colon and Rectal Surgery, 2019)
The Surveillance, Epidemiology, and End Results (SEER) program is a clinical database, funded by the National Cancer Institute (NCI), which was created to collect cancer incidence, prevalence, and survival data from U.S. cancer registries. By capturing approximately 30% of the U.S. population, it serves as a powerful resource for researchers focused on understanding the natural history of colorectal cancer and improvement in patient care. The linked SEER-Medicare database is a robust database allowing investigators to perform studies focusing on health disparities, quality of care, and cost of treatment in oncologic disease. Since its infancy in the early 1970s, the database has been utilized for thousands of studies resulting in novel publications that have shaped our management of colorectal cancer among other malignancies.
Keywords: SEER; SEER-Medicare; outcomes research; colon cancer; rectal cancer